Replicação de arquivos com Java - Werlang, Rodrigo (2000)
The objective of this work is to supply one more contribution to the scientific community presenting techniques that will be used in distributed systems that need file replications in real time guaranteeing the permanent availability of the system. As the replication model is based on Java, portability tests and performance were also accomplished in the Linux and Windows platforms, allowing the use of methods for multithreading to manage the connections. To accomplish the replication in real time, it was necessary to develop new classes for insert, removal and updating of bytes in files, once they didn't exist in Java, updating only the modified bytes and putting back dynamically the others.